Positive electrode for lithium ion electrochemical element

By using a mixture of monocrystalline lithium nickel manganese oxide and lithium manganese iron phosphate in the positive electrode of lithium-ion batteries, the problems of inaccurate state-of-charge detection and nickel-manganese dissolution in lithium-ion batteries have been solved, resulting in longer battery life and higher safety.

CN121002671APending Publication Date: 2025-11-21SAFT GRP SA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480023238.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-29
Filing Date
2024-03-28
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the positive electrode based on LMFP is difficult to accurately detect the state of charge, especially in the range of 30% to 80% where the voltage change is small. This leads to a sharp increase in battery voltage during overcharging, which affects battery life. Furthermore, the dissolution of manganese and nickel when using NMC and NCA oxides reduces battery capacity.

Method used

A mixture of active materials is used, comprising single-crystal lithium nickel manganese oxide (NMx) and lithium manganese iron phosphate (LMFP). By adjusting the stoichiometric index of nickel, manganese and cobalt, the dissolution of nickel and manganese is reduced and the accuracy of charge termination detection is improved. The proportion of active materials ranges from 10% to 70% NMx and 90% to 30% LMFP.

Benefits of technology

It improves the accuracy of state-of-charge detection for lithium-ion batteries, reduces the dissolution of nickel and manganese, extends battery life, and provides a greater safety margin at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121002671A_ABST
    Figure CN121002671A_ABST
Patent Text Reader

Abstract

An electrode comprising a mixture of active materials comprising:-a lithium nickel manganese oxide of the formula Li Ni < 1-x-y-z > Mn < x > Co < y > M < z > O < 2 >, where 0.9 < = a < = 1.1, 0.60 < = 1-x-y-z < lt; 0.80, 0 lt; x, 0 < = y < = 0.02, 0 < = z, M is one or more elements selected from the group consisting of Al, B, Mg, Si, Ca, Ti, V, Cr, Fe, Cu, Zn, Y, Zr, Nb, W, Mo, S, Sr, Ce, Ga, Ta, Nd, Pr and La; and-a lithium ferromanganese phosphate of the formula Li < x > Mn < 1-y-z > Fe < y > M < z > PO4, with 0.8 < = x < = 1.2, 0.5 < = 1-y-z < lt; 1, 0lt; y < = 0.5, 0 < = z < = 0.2, and M is one or more elements selected from the group consisting of Al, B, Mg, Si, Ca, Ti, V, Cr, Co, Cu, Ni, Zn, Y, Zr, Nb, W, and Mo.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The technical field of the invention is the technical field of active materials intended for the cathode, that is to say the positive electrode, of a lithium-ion electrochemical cell, also called lithium-ion battery. BACKGROUND

[0002] Lithium-ion electrochemical cells comprising a positive electrode whose active material is based on at least one lithium phosphate of a transition metal are known in the prior art. The lithium phosphate of at least one transition metal generally has the formula LiMPO4, in which M represents at least one transition metal, for example Mn, Co, Ni, Fe or Mn together with Fe. When manganese is combined with iron, the lithium phosphate is abbreviated LMFP.

[0003] Determining the state of charge of a cell whose positive electrode comprises LMFP is difficult. Indeed, for a state of charge generally between 30% and 80%, such a cell has a so-called "flat" charge curve. The charge curve is understood to mean a curve representing the variation in voltage of the cell as a function of time during charging. In the range of state of charge between 30% and 80%, the voltage of the cell increases very little, so it is difficult to correlate the voltage of the cell with its state of charge. Furthermore, when the end of charge is approached, that is to say for a state of charge of about 95% to 100%, the voltage of the cell increases sharply. Indeed, the de-lithiation of almost all the lithium present in the lithium phosphate leads to a sudden increase in voltage. This surge means that it is not possible to alert the user early enough that overcharging is about to occur. The voltage of the cell can quickly reach high values. Long exposure of the cell to overcharging leads to degradation of the electrolyte and to a reduction in the lifetime of the cell.

[0004] Methods of detecting the end of charge of a cell having a positive electrode based on LMFP have been sought in order to alert the user early enough that the cell is about to be fully charged. For example, document FR 3122286 teaches the use of oxides of nickel, manganese and cobalt rich in nickel, abbreviated NMC, or oxides of lithium, nickel, cobalt and aluminium also rich in nickel, abbreviated NCA, in mixture with LMFP. The term "rich in nickel" means that the stoichiometric index of nickel of the NMC is at least 0.80. It specifies that the stoichiometric index of nickel of the NCA is at least 0.83.

[0005] However, a progressive dissolution of the manganese and nickel of the NMC and NCA oxides in the electrolyte of the cell is observed. The consequence of this dissolution is a progressive decrease in the discharge capacity of the cell and therefore a reduction in its lifetime. Thus, it is sought to reduce the dissolution of manganese and nickel while maintaining the possibility of accurately determining the end of charge of a cell whose positive electrode is based on LMFP. SUMMARY

[0006] To this end, the invention provides an electrode comprising a mixture of active materials, said mixture comprising:

[0007] - formula Li a Ni 1-x-y-z Mn x Co y M z O2monocrystalline lithium nickel manganese oxide (NMx), wherein 0.9≤a≤1.1, 0.60≤1-x-y-z<0.80, 0<x, 0≤y≤0.02, 0≤z, M is one or more elements selected from the group consisting of Al, B, Mg, Si, Ca, Ti, V, Cr, Fe, Cu, Zn, Y, Zr, Nb, W, Mo, S, Sr, Ce, Ga, Ta, Nd, Pr and La; and

[0008] - formula Li x Mn 1-y-z Fe y M z PO4lithium manganese iron phosphate (LMFP) of formula Li

[0009] It has been found that by using monocrystalline NMxand selecting the stoichiometric indices of nickel, manganese and cobalt in the following ranges, respectively: 0.60≤1-x-y-z<0.80, 0<x and 0≤y≤0.2, it is possible to reduce the dissolution of nickel and manganese while maintaining or improving the ability to accurately detect the end of charge of the battery.

[0010] According to one embodiment, the mixture of active materials consists of:

[0011] - 10% to 70% or 20% to 40% by mass of monocrystalline lithium nickel manganese oxide;

[0012] - 90% to 30% or 80% to 60% by mass of lithium manganese iron phosphate.

[0013] According to one embodiment, in the monocrystalline lithium nickel manganese oxide, 0.60<1-x-y-z or 0.60<1-x-y-z≤0.75.

[0014] According to one embodiment, in the monocrystalline lithium nickel manganese oxide, 0.005≤y≤0.015 or y=0.

[0015] According to one embodiment, the particle size distribution of the monocrystalline lithium nickel manganese oxide is characterized by a volume median diameter Dv 50 in the range of 1 μm to 7 μm, preferably in the range of 1 μm to 4 μm.

[0016] According to one embodiment, in lithium manganese iron phosphate, 0.7 ≤ 1 - y - z ≤ 0.9.

[0017] The present invention also relates to a lithium-ion electrochemical cell, comprising: at least one positive electrode, said at least one positive electrode being the above electrode; and at least one negative electrode.

[0018] According to one embodiment, said at least one negative electrode comprises an active material selected from graphite, silicon, titanium oxide, lithium titanium oxide, titanium and niobium oxides, and mixtures thereof.

[0019] The present invention also relates to a method for improving the detection of the end of charging of a lithium-ion electrochemical cell, said lithium-ion electrochemical cell comprising a positive electrode containing lithium manganese iron phosphate of the formula Li x Mn 1-y-z Fe y M z PO4, where 0.8 ≤ x ≤ 1.2, 0.5 ≤ 1 - y - z < 1, 0 < y ≤ 0.5, 0 ≤ z ≤ 0.2, and M is one or more elements selected from Al, B, Mg, Si, Ca, Ti, V, Cr, Co, Cu, Ni, Zn, Y, Zr, Nb, W, and Mo, said method comprising:

[0020] a) During the manufacture of the positive electrode, replacing a part of the lithium manganese iron phosphate with single crystal lithium nickel manganese oxide of the formula Li a Ni 1-x-y-z Mn x Co y M z O2, where 0.9 ≤ a ≤ 1.1, 0.60 ≤ 1 - x - y - z < 0.80, 0 < x, 0 ≤ y ≤ 0.02, 0 ≤ z, and M is one or more elements selected from Al, B, Mg, Si, Ca, Ti, V, Cr, Fe, Cu, Zn, Y, Zr, Nb, W, Mo, S, Sr, Ce, Ga, Ta, Nd, Pr, and La;

[0021] b) Correlating the voltage of the cell with its state of charge.

[0022] The method can be implemented when the positive electrode of the cell is as described above. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Embodiments of the present invention are described in more detail below with reference to the drawings.

[0024] Figure 1 shows the charge / discharge curves during the first cycle of a cell comprising positive electrodes A to E of the examples.

[0025] Figure 2 shows the curves dQ / dV of the active materials of electrodes A and electrode B.​

[0026] [ Figure 3 ] shows the differential scanning calorimetry curve obtained on the mixture of active materials regarding electrode C and electrode D. DETAILED DESCRIPTION

[0027] Positive electrode

[0028] At least one positive electrode of the battery comprises a current collector, at least one face of which is coated with a layer of a composition of active materials. A "composition of active materials" is understood to mean a composition comprising a mixture of active materials, and optionally one or more binders and one or more conductive materials.

[0029] The positive current collector is a solid or porous metal strip that can be made of aluminum or an aluminum alloy, or steel or stainless steel. Its thickness can be in the range of 6 μιη to 30 μιη or 5 μιη to 20 μιη or 10 μιη to 15 μιη, preferably 10 μιη to 15 μιη.

[0030] Before coating the current collector with the layer of composition of active materials, the current collector can be coated on one of its faces or on both of its faces with a coating intended to improve the electronic conductivity between the layer of composition of active materials and the strip and / or intended to improve the adhesion of the layer of composition of active materials to the strip. The coating material can be chosen from carbon, graphite, carbon fibers, carbon nanotubes and mixtures thereof. It is preferably made of carbon. The coating material can be obtained by coating the strip with a dispersion of this material, then evaporating the solvent in the dispersion, or it can be obtained by sputtering. Only certain portions of the strip can be coated with the coating material. The coated portions can be separated from one another by predetermined or periodic intervals ("intermittent coating"). The intermittent coating is preferably present on both sides of the strip. It facilitates the handling of the electrode. In one variant, one or both faces of the strip can undergo a surface treatment intended to increase the adhesion of the layer of composition of active materials to the strip. It can be a surface treatment that creates a roughness or a micro-roughness, such as a chemical etching or a laser treatment.

[0031] The mixture of active materials comprises at least one single-crystal lithium nickel manganese oxide NMx and at least one lithium manganese iron phosphate LMFP. A single crystal is a solid composed of a single crystal formed from a single seed crystal. The synonymous terms that can be used are single-crystal material or single-crystal material, which are commonly referred to by those skilled in the art as "single crystals". The terms single crystal or single-crystal are also used to refer to a morphology in which the secondary particles ideally consist of a single primary particle.

[0032] NMx is of formula (I) Li a Ni 1-x-y-z Mn x Co y M zCompounds of formula O2, wherein 0.9 < a < 1.1, 0.60 < 1-x-y-z < 0.80, 0 < x, 0 < y < 0.02, 0 < z, M is one or more elements selected from the group consisting of Al, B, Mg, Si, Ca, Ti, V, Cr, Fe, Cu, Zn, Y, Zr, Nb, W, Mo, S, Sr, Ce, Ga, Ta, Nd, Pr and La.

[0033] A stoichiometric index of nickel of at least 0.60 provides a positive electrode with sufficiently high electrochemical capacity. In one embodiment, 0.65 < 1-x-y-z < 0.80 or 0.70 < 1-x-y-z < 0.80 or 0.75 < 1-x-y-z < 0.80. Conversely, a stoichiometric index of nickel greater than or equal to 0.8 adversely affects the stability of the lithium nickel oxide when exposed to high temperatures or potentials greater than 4.3 V vs. Li. From a thermal and electrochemical point of view, a stoichiometric index of between 0.6 and less than 0.8, preferably about 0.75, makes it possible to provide a positive electrode with both high electrochemical capacity and good stability.

[0034] According to one embodiment, the stoichiometric index of manganese is in the range 0.20 < x < 0.40 or 0.25 < x < 0.30.

[0035] According to one embodiment, the stoichiometric index of cobalt is in the range 0.001 < y < 0.015 or 0.005 < y < 0.010 or 0.001 < y < 0.005. Preferably, y = 0. A small amount of cobalt or even no cobalt at all in NMx solves the problem of cobalt scarcity.

[0036] According to one embodiment, z = 0.

[0037] According to one embodiment, y = 0 and z = 0.

[0038] According to one embodiment, y = 0, z = 0, 0.20 < x < 0.40 and 0.60 < 1-x < 0.80.

[0039] According to one embodiment, y = 0, z = 0, 0.20 < x < 0.30 and 0.70 < 1-x < 0.80.

[0040] An example of a preferred compound is LiNi 0.65 Mn 0.35 O2, LiNi 0.70 Mn 0.30 O2 and LiNi 0.75 Mn 0.25 O2.

[0041] The Applicant has found that the tendency of NMx to release nickel and manganese into the electrolyte is less than that of LiNi0.8 Mn 0.1 Co 0.1 O2(NMC811) trend. This advantage can be attributed on one hand to the single crystalline nature of NMx and on the other hand to the different stoichiometric coefficients of nickel, manganese and cobalt. Thus, with respect to a battery whose positive electrode would contain NMC811, the present application makes it possible to increase the lifetime of the battery.

[0042] The parameter characterizing the size distribution of the single crystals is the median volume diameter Dv 50 . The expression "median volume diameter Dv 50 " means that, in a given population of particles, 50% by volume of the particles consist of particles for which the equivalent diameter is less than the Dv 50 value and 50% by volume of the particles consist of particles for which the equivalent diameter is equal to or greater than the Dv 50 value. The expression "equivalent diameter" of a particle refers to the diameter of a sphere having the same volume as the particle. The Dv 50 of NMx is generally in the range 1 to 7 pm or 1 to 4 pm. A value greater than 7 pm will generally indicate that it is polycrystalline. The Dv 50 may be measured using laser diffraction techniques.

[0043] The space group of the single-crystal NMx is the P3121 group (trigonal system). The space group of the single-crystal NMx can be confirmed by X-ray diffraction to be the P3121 group.

[0044] According to one embodiment, the NMx particles are free of any coating, in particular a coating consisting of LMFP or a coating of metal oxides.

[0045] The LMFP is a compound of formula (II) Li x Mn 1-y-z Fe y M z PO4, wherein 0.8 < x < 1.2, 0.5 < 1-y-z < 1, 0 < y < 0.5, 0 < z < 0.2, M is one or more elements selected from the group consisting of Al, B, Mg, Si, Ca, Ti, V, Cr, Co, Cu, Ni, Zn, Y, Zr, Nb, W and Mo.

[0046] According to one embodiment, 0.5 < 1-y-z < 1 or 0.7 < 1-y-z < 0.9 or 0.75 < 1-y-z < 0.80.

[0047] Examples of preferred LMFP compounds are LiMn 0.8 Fe 0.2 PO4, LiMn 0.78 Fe 0.22 PO4, LiMn​0.7 Fe 0.3 PO4, LiMn 2 / 3 Fe 1 / 3 PO4 and LiMn 0.5 Fe 0.5 PO4.

[0048] LMFP can be coated with carbon or carbon nanotubes.

[0049] LMFPs can exist as unconnected particles (also known as primary particles) or as aggregates of primary particles (also known as secondary particles). LMFPs can have a median volume diameter Dv. 50 In the form of secondary particles in the range of 1 μm to 15 μm or 1.5 μm to 4 μm.

[0050] The ratio of LMFP to NMx in the active material mixture can be as follows:

[0051] Single-crystal NMx comprising 10% to 70% by mass, and

[0052] LMFP by weight, or

[0053] Single-crystal NMx comprising 20% ​​to 40% by mass, and

[0054] 80% to 60% LMFP by weight, or

[0055] Single-crystal NMx comprising 25% to 35% by mass, and

[0056] LMFP by weight: 75% to 65%.

[0057] This invention excludes LMFP active materials as coatings for NMx particles.

[0058] The active material composition may comprise a plurality of single-crystal lithium nickel manganese oxides of formula (I) and a plurality of lithium manganese iron phosphates of formula (II). Preferably, the active material composition does not contain any active material other than the compounds of formula (I) or (II).

[0059] Binders commonly used in active material compositions enhance the cohesive forces between particles of the active material and improve the adhesion of the active material composition layers to the current collector. Binders may contain one or more of the following compounds: polyvinylidene fluoride (PVDF) and its copolymers, polytetrafluoroethylene (PTFE) and its copolymers, polyacrylonitrile (PAN), poly(methyl methacrylate) or poly(butyl methacrylate), poly(vinyl chloride) (PVC), poly(vinyl alcohol formaldehyde), polyesters, block polyether amides, polymers of acrylic acid, methacrylic acid, acrylamide, itaconic acid, sulfonic acid, elastomers, and cellulose compounds such as carboxymethyl cellulose (CMC). Elastomers that can be used as binders may be selected from styrene-butadiene (SBR), butadiene-acrylonitrile (NBR), and hydrogenated butadiene-acrylonitrile (HNBR). The binder may constitute 1% to 10%, 1% to 5%, or 2% to 5% of the dry composition of the active material by mass.

[0060] The conductive material is typically selected from graphite, carbon black, acetylene black, carbon black, graphene, carbon fiber, single-walled carbon nanotubes, multi-walled carbon nanotubes, and mixtures thereof. It may comprise 0.1% to 10% or 0.1% to 5% of the dry composition of the active material.

[0061] Preparation of positive electrode

[0062] Ink is prepared by dispersing one or more LMFP active materials and one or more NMx active materials in a solvent or mixture of solvents. Optionally, a binder and a conductive material are added to the dispersion. The viscosity of the ink can be varied by changing the amount of solvent incorporated into the mixture, and then it is deposited onto one side of a current collector. The ink-coated current collector is dried and then laminated to adjust its thickness. After solvent evaporation, a layer of the active material composition is obtained, the proportions of which are typically:

[0063] - 80% to 98% or 90% to 95% of the positively active material by weight.

[0064] - 1% to 10% or 2% to 5% by weight of adhesive,

[0065] - 0.1% to 10% or 2% to 5% conductive material by weight.

[0066] negative electrode

[0067] At least one negative electrode includes a current collector, at least one of its two faces of which is coated with a layer of a composition of negatively active materials. The negatively active material composition comprises at least one negatively active material, as well as optionally a binder and a conductive material. The negative electrode current collector is a solid or porous metal strip that may be made of copper or a copper-based alloy. Its thickness may range from 3 μm to 10 μm, preferably from 5 μm to 8 μm.

[0068] Before coating the current collector with a layer of the active material composition, the current collector may be coated on one or both sides with a coating designed to improve the electronic conductivity between the layer of the active material composition and the strip and / or improve the adhesion of the layer of the active material composition to the strip. The coating materials and coating deposition process can be the same as those described for current collectors for positive electrodes.

[0069] The negatively active material is preferably selected from carbon, graphite, coke, carbon black, glassy carbon, silicon, silicon-carbon composites, silicon carbide, titanium oxide, lithium titanium oxide, titanium and niobium oxides, and mixtures thereof. Titanium oxide may be selected from H₂Ti₆O. 13 H2Ti 12 O 25 And TiO2. Lithium titanium oxides can be selected from Li4Ti5O. 12 Li₂TiO₃, Li₂Ti₃O₇, LiTi₂O₄ and Li₂Na₂Ti₆O 14 Titanium niobium oxides can be selected from TiNb₂O₇, Ti₂Nb₂O₉, and Ti₂Nb. 10 O 29 .

[0070] Method for preparing negative electrodes

[0071] The negative electrode is prepared in a conventional manner. The ink is prepared by optionally dispersing one or more negatively active materials together with a binder in a solvent or mixture of solvents. The binder can be, for example, those described with respect to the positive electrode.

[0072] The ink-coated current collector is dried and then laminated to adjust its thickness. This yields the negative electrode.

[0073] After the solvent in the ink evaporates, the typical proportions of the components in the negatively active material composition layer are:

[0074] - 85% to 98% or 90% to 98% negatively reactive materials by weight.

[0075] - 1% to 10% or 1% to 5% by weight of adhesive,

[0076] - 0% to 5% or 1% to 5% conductive material by weight.

[0077] electrolyte

[0078] The electrolyte can be a liquid. It is obtained by dissolving one or more lithium salts in one or more organic solvents. The solvent can be selected from saturated cyclic carbonates, unsaturated cyclic carbonates, acyclic carbonates, alkyl esters, ethers, nitrile solvents, and tetrahydrothiophene dioxide (sulfolane).

[0079] Saturated cyclic carbonates include ethylene carbonate (EC), fluoroethylene carbonate (FEC), propylene carbonate (PC), butyl carbonate (BC), and mixtures thereof.

[0080] Unsaturated cyclic carbonates include vinylene carbonate (VC).

[0081] Acyclic carbonates include dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dipropyl carbonate (DPC), and mixtures thereof.

[0082] Alkyl esters include methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, and mixtures thereof.

[0083] Ethers include dimethyl ether (DME), diethyl ether (DEE), and mixtures thereof.

[0084] Lithium salts can be selected from lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium hexafluoroantimonyate (LiSbF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(fluorosulfonyl)imide (Li(FSO2)2N) (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiN(CF3SO2)2) (LiTFSI), and lithium tri(fluoromethanesulfonyl)methyl (LiC(CF3SO4)2) (LiFSO4). 2) Lithium bis(pentafluoroethylsulfonyl)imide LiN(C2F(SO2)2(LiBeTI), lithium 4,5-dicyano-2-(trifluoromethyl)imidazolium (LiTDI), lithium bis(oxalate)borate (LiBOB), lithium difluoro(oxalate)borate (LIDFOB), lithium tri(pentafluoroethyl)trifluorophosphate LiPF3(CF2CF3)3(LiFAP), lithium difluorophosphate LiPO2F2 and mixtures thereof.

[0085] The concentration of the at least one lithium salt can be in the range of 0.75 mol / L to 1.5 mol / L. It is preferably in the range of 1 mol / L to 1.5 mol / L. Even more preferably, it is in the range of 1 mol / L to 1.2 mol / L.

[0086] Separator:

[0087] A separator is positioned between the positive and negative electrodes. The separator can be made of materials selected from: polyolefins (e.g., polypropylene (PP), polyethylene (PE), polyesters, polymer-bonded glass fibers, polyimides, polyamides, polyaramids, polyamide-imides, and cellulose. Polyesters can be selected from polyethylene terephthalate (PET) and polybutylene terephthalate (PBT). Advantageously, the polyester, polypropylene, or polyethylene contains or is coated with a ceramic material selected from metal oxides, carbides, nitrides, borides, silicides, and sulfides. This ceramic material can be SiO2 or Al2O3. The separator can be a ceramic-coated polyolefin layer, preferably a polyethylene layer coated with ceramic on both sides.

[0088] Preparation of electrochemical beams:

[0089] An electrochemical plate assembly is formed by inserting a separator between at least one positive electrode and at least one negative electrode. The electrochemical plate assembly is inserted into a battery container. The battery container can be parallelepiped or cylindrical. In the latter case, the electrochemical plate assembly is spiral-shaped to form a cylindrical assembly of electrodes.

[0090] Filling and closing containers:

[0091] For example, a cover can be assembled onto a battery container using laser welding. The battery container is filled with electrolyte. For this purpose, the cover may include a filling hole through which the electrolyte is introduced. After the electrolyte is introduced, the filling hole is sealed by said ball through which a stainless steel ball is electrowelded.

[0092] Example:

[0093] Five positive electrodes, A through E, were prepared. They differ in their active materials. Table 1 shows the active materials used. In this table, LMFP is LiMn. 0.78 Fe 0.22 PO4; NMx is single-crystal LiNi 0.75 Mn 0.25 O2, and NMC811 for LiNi 0.80 Mn 0.1 Co 0.1 O2.

[0094] Table 1

[0095]

[0096] *Non-invented electrode

[0097] The electrodes were exposed to a voltage of 4.5 V relative to Li metal for 7 days. After these 7 days of exposure to 4.5 V, the amount of metal released from the positive electrode and found on the negative electrode was measured. Table 2 presents the obtained measurement results.

[0098] Table 2

[0099]

[0100] *Non-invented electrode

[0101] **The amount of nickel or manganese measured at the negative electrode at the end of the test and expressed as a percentage of the corresponding amount initially present at the positive electrode.

[0102] Electrode C, containing a mixture of NMx and LMFP, was found to release the lowest amounts of nickel and manganese. This result was unexpected. In fact, electrode C released 40% less nickel than electrode D, yet the stoichiometric index of nickel was only 0.75 in NMx and 0.80 in NMC811, meaning it was only 6% lower in NMx. Furthermore, regarding manganese, the percentage of manganese released by the electrode was not proportional to the stoichiometric index of manganese in the lithium oxide. In fact, NMx contained 2.5 times more manganese than NMC811. However, electrode C, containing NMx, released less manganese than electrode D, containing NMC811.

[0103] The applicant also observed that replacing NMC811 with NMx in a mixture with LMFP improved the accuracy of determining the state of charge of the battery when the battery is close to its full state of charge.

[0104] Charge / discharge profiles for five batteries, A through E, including a lithium metal negative electrode, have been plotted between 2.5 V and 4.45 V. They are... Figure 1 The first loop is shown in the diagram.

[0105] The voltage of battery B, which includes NMC811, varies proportionally with the battery's state of charge until approximately 80% of its full charge. Above 80%, the charge / discharge curve has a horizontal plateau, making it inaccurate to determine the battery's state of charge based solely on its voltage information. The voltage of battery A, which includes NMx, also varies proportionally with its state of charge, even above 80% of its full charge. Therefore, the use of NMx allows for more accurate detection of the end of charging.

[0106] The charge / discharge curve of battery E, which contains only LMFPs, exhibits two plateaus: a first plateau P1 at approximately 3.50 V attributed to iron and a second plateau P2 at approximately 4.1 V attributed to manganese. Due to the sudden voltage rise at the end of the second plateau P2, detecting the approaching end of charging is difficult. Replacing 30% of the LMFPs with NMC811 (curve D) allows for an increase in the mass capacity of the electrode on the one hand, and on the other hand, a gradual increase in voltage near the end of charging in the form of a sloping portion (Ia) with its midpoint at approximately 4.2 V. Replacing 30% of the LMFPs with NMx (curve C) also increases the capacity per unit mass relative to LMFPs alone, but it also increases the voltage of the sloping portion Ib to approximately 4.3 V, instead of the 4.2 V of the sloping portion Ia. The difference between the sloping portion Ib and the manganese plateau P2 at 4.1 V is greater than the difference between the sloping portion Ia and the manganese plateau P2 at 4.1 V. This larger difference allows for a more accurate correlation between the battery voltage and its state of charge.

[0107] The applicant has discovered that NMx exhibits better oxidation stability than NMC811 when the applied potential exceeds 4.3 V relative to Li. Figure 2 The dQ / dV curves for active materials A (NMx) and B (NMC811) were compared. A high-intensity peak at approximately 4.2 V indicates significant structural degradation of NMC811 at this potential. This suggests that charging NMC811 above 4.2 V significantly degrades the material's structure. In contrast, NMx exhibits a much lower peak intensity than NMC811. Furthermore, the peak of NMx appears above 4.2 V. Therefore, NMx can be charged to 4.45 V without significant structural degradation. This advantage is applied in this invention to utilize a wider potential range up to 4.45 V, instead of 4.3 V for NMC811, thereby increasing the accuracy of determining the state of charge near the end of charging. All these results demonstrate the potential for improved detection of the end of charging while reducing the dissolution of nickel and manganese.

[0108] Another benefit of replacing NMC811 with NMx is that it provides a greater safety margin for battery users in the event of elevated temperatures. Differential scanning calorimetry (DSC) techniques have been used to detect the temperature at which the mixture of active materials of electrodes C and D begins to release heat when electrode D is subjected to elevated temperatures. Figure 3 The results shown indicate that for the mixture of active materials for the non-inventive electrode D, heat release begins at 200°C, while for the mixture of active materials for electrode C, approximately 230°C is required for heat release to be observed.

[0109] Finally, compared to batteries whose active material is only LMFP, replacing a portion of LMFP with NMx increases both the energy per unit mass and the capacity per unit mass. This is demonstrated by the results in Table 3.

[0110] [Table 3]

[0111]

[0112] *Non-invented electrode

Claims

1. An electrode comprising a mixture of active materials, said mixture comprising: -type Li a Ni 1-x-y-z Mn x Co y M z single crystal lithium nickel manganese oxide of O2, where 0.9 ≤ a ≤ 1.1, 0.60 ≤ 1 - x - y - z < 0.80, 0 < x, 0 ≤ y ≤ 0.02, 0 ≤ z, and M is one or more elements selected from Al, B, Mg, Si, Ca, Ti, V, Cr, Fe, Cu, Zn, Y, Zr, Nb, W, Mo, S, Sr, Ce, Ga, Ta, Nd, Pr, and La; and -type Li x Mn 1-y-z Fe y M z lithium manganese iron phosphate of PO4, where 0.8 ≤ x ≤ 1.2, 0.5 ≤ 1 - y - z < 1, 0 < y ≤ 0.5, 0 ≤ z ≤ 0.2, and M is one or more elements selected from Al, B, Mg, Si, Ca, Ti, V, Cr, Co, Cu, Ni, Zn, Y, Zr, Nb, W, and Mo.

2. The electrode according to claim 1, wherein the mixture of active materials comprises: - 10% to 70% by mass of monocrystalline lithium nickel manganese oxide; - 90% to 30% lithium manganese iron phosphate by weight.

3. The electrode according to claim 2, wherein the mixture of active materials comprises the following: - 20% to 40% by mass of monocrystalline lithium nickel manganese oxide; - 80% to 60% lithium manganese iron phosphate by weight.

4. The electrode according to any one of the preceding claims, wherein in the single-crystal lithium nickel manganese oxide, 0.60 < 1-xyz.

5. The electrode according to any one of claims 1 to 3, wherein in the single-crystal lithium nickel manganese oxide, 0.60 < 1-xyz ≤ 0.

75.

6. The electrode according to any one of the preceding claims, wherein in the single-crystal lithium nickel manganese oxide, 0.005 ≤ y ≤ 0.

015.

7. The electrode according to any one of claims 1 to 5, wherein in the single-crystal lithium nickel manganese oxide, y = 0.

8. The electrode according to any one of the preceding claims, wherein the particle size distribution of the single-crystal lithium nickel manganese oxide is characterized by a median volume diameter Dv 50 The range is from 1 μm to 7 μm, preferably from 1 μm to 4 μm.

9. The electrode according to any one of the preceding claims, wherein in the lithium manganese iron phosphate, 0.7 ≤ 1-yz ≤ 0.

9.

10. A lithium-ion electrochemical battery, comprising: - At least one positive electrode, said at least one positive electrode being an electrode according to any one of claims 1 to 9; - At least one negative electrode.

11. The lithium-ion electrochemical battery according to claim 10, wherein the at least one negative electrode comprises an active material selected from graphite, silicon, titanium oxide, lithium titanium oxide, titanium and niobium oxide, and mixtures thereof.

12. A method for improving the detection of the end of charging of a lithium-ion electrochemical cell, the lithium-ion electrochemical cell comprising a positive electrode of lithium manganese iron phosphate containing Li x Mn 1-y-z Fe y M z PO4, where 0.8 ≤ x ≤ 1.2, 0.5 ≤ 1 - y - z < 1, 0 < y ≤ 0.5, 0 ≤ z ≤ 0.2, and M is one or more elements selected from Al, B, Mg, Si, Ca, Ti, V, Cr, Co, Cu, Ni, Zn, Y, Zr, Nb, W, and Mo, the method comprising: a) During the manufacture of the positive electrode, a single crystal lithium nickel manganese oxide of the formula Li a Ni 1-x-y-z Mn x Co y M z O2 is used to replace a part of lithium manganese iron phosphate, where 0.9 ≤ a ≤ 1.1, 0.60 ≤ 1 - x - y - z < 0.80, 0 < x, 0 ≤ y ≤ 0.02, 0 ≤ z, and M is one or more elements selected from Al, B, Mg, Si, Ca, Ti, V, Cr, Fe, Cu, Zn, Y, Zr, Nb, W, Mo, S, Sr, Ce, Ga, Ta, Nd, Pr, and La; b) Associating the voltage of the battery with its state of charge.

13. The method of claim 12, wherein the positive electrode is the electrode according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Mixture of active materials for lithium-ion element cathode

    FR3122286A1